Perubahan Perilaku Menyampah Siswa Melalui “Reinforcement” - Vanda Ningrum; Deshinta Vibriyanti; Inayah Hidayati; Intan Adhi Perdana Putri; Luh Kitty Katherina; Sari Seftiani (Jurnal Sosial Humaniora, 2021)
Littering behavior studies are essential amid high waste conditions inIndonesia. This study aims to analyze student littering behavior changesthrough a reinforcement program in Junior High School in Depok, WestJava. Using an explorative-qualitative approach and collecting data throughin-depth interviews with key informants, the study found that students'littering behavior can be categorized as active and passive. Active litteringbehavior is based on students' lack of concern for the environment due toinsufficient knowledge of the impact of waste. Then passive litteringbehavior is caused by habits that delay littering even though they are awareof the waste dangers. Continuous reinforcement at school in positive andnegative reinforcement through the "Green School Program" can reducestudent littering behavior, both actively and passively.